Інформаційна технологія аналізу динаміки вуглецевого балансу лісів Польщі - Стрямець, С. П.; Стрямець, Г. В.; Stryamets, S. P.; Striamets, H. V. (Видавництво Львівської політехніки, 2021)
Ведення лісового господарства пов'язане з використанням значних земельних площ і великою кількістю пов'язаної з ними інформації. Тому для оброблення, аналізу і візуалізації інформації в лісових екосистемах логічним є використання геоінформаційних систем (ГІС). Зелені рослини, дерева, що депонують вуглець і утримують його тривалий час, є основними поглиначами вуглецю на суші, тому дослідження приросту деревини, нагромадження фітомаси в лісових екосистемах необхідне для визначення вуглецевого балансу. Розроблено інструментарій визначення георозподіленої фітомаси лісів для розрахунку депонованого вуглецю за статистичними даними запасу насадження, породного складу, класу віку та інших лісівничо-таксаційних показників, які наводяться офіційними джерелами. Наведено опис лісів Польщі, засобами ГІС проведено аналіз табличних даних таксаційних показників лісових екосистем, наведено діаграми та створено цифрові карти лісів. Проведено аналіз стану лісів окремих воєводств Польщі у 2009 та 2019 роках на предмет оцінки викидів та поглинання парникових газів лісовими екосистемами. Описано трирівневу схему інвентаризації парникових газів, рекомендовану методикою IPCC. Наведено порівняльний аналіз лісівничо-таксаційних показників лісів Польщі за період від 2009 до 2019 років та методи, які використовують для обчислення емісій та поглинань парникових газів. Визначено кількість депонованого вуглецю за десятирічний період лісовими екосистемами Польщі. Удосконалено та доповнено архітектуру геоінформаційної технології просторового аналізу процесів депонування вуглецю та емісії парникових газів у секторі лісового господарства Польщі. Проведено розрахунки депонованого вуглецю за статистичними даними запасу насадження, породного складу, класу віку та інших лісівничо-таксаційних показників, які наводяться офіційними джерелами.

Forest management involves the use of large areas of land and a large amount of related information. Therefore, the use of geographic information technologies (GIS) is substantiated for the processing, analysis, and visualization of information in forest ecosystems. Green plants and trees deposit carbon and retain it for a long time, they are the main absorbers of carbon on land, so to determine the carbon balance the study of wood growth, accumulation of phytomass in forest ecosystems is necessary. The purpose of the work is to develop a toolkit for determining the geo-distributed phytomass of forests for the calculation of deposited carbon according to statistical data of planting stock, species composition, age class, and other silvicultural and taxonomic indicators provided by the official sources. The article provides a description of Polish forests, GIS analysis of tabular data on taxonomic indicators of forest ecosystems, diagrams, and digital maps of forests. The analysis of the forests state in some voivodships of Poland in 2009 and 2019 was conducted to assess emissions and removals of greenhouse gases by forest ecosystems. The three-level scheme of greenhouse gas inventory recommended by the IPCC technique is described. To carry out the inventory, a multilevel mathematical model is used, which includes: the highest level of inventory (level of national inventory), the middle level of inventory (level of region or district), and the inventory lowest level (level of the elementary plots). A comparative analysis of forestry and tax indicators of Polish forests for the period from 2009 to 2019 and the methods used to calculate greenhouse gas emissions and removals are presented. The amount of carbon deposited over a ten-year period by Polish forest ecosystems has been determined. The architecture of geographic information technology for spatial analysis of carbon deposition and greenhouse gas emissions in the Polish forestry sector has been improved and supplemented. Calculations of the deposited carbon were made according to statistical data of planting stock, species composition, age class, and other silvicultural and taxonomic indicators, which are taken from the official sources. The geoinformation approach to the comparative analysis of greenhouse gases for different time intervals is based on the use of the appropriate digital map layers, mathematical models of inventory, statistical information on business results, as well as the use of a number of other specific parameters describing complex greenhouse gas emission and absorption processes.
Information technology for the analysis of the dynamic of the carbon balance of forests in Poland
Keywords: ГІС; цифрові карти; парникові гази; ліси Польщі; GIS; digital maps; greenhouse gases; forests of Poland